1961
DOI: 10.5962/bhl.title.58940
|View full text |Cite
|
Sign up to set email alerts
|

Water relations and forest distribution in the Douglas-fir region on Vancouver Island /

Abstract: Trees per acre Basal area (sq. ft. per acre) Volume (cu. ft. per acre) Tsuga heterophylla Av. height, dom. and codom. (ft.) Av. diam., dom. and codom. (in.) Av. age, dom. and codom. (years) Trees per acre Basal area (sq. ft. per acre) Volume (cu. ft. per acre) Thuja plicata Av. height, dom. and codom. (ft) Av. diam., dom. and codom. (in.) Av. age, dom. and codom. (years) Trees per acre Basal area (sq. ft. per acre) Volume (cu. ft. per acre) Shrub Layer (Line interception) Gaultheria shallon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1963
1963
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The confidence level for the mean of the total throughfall percentages for the storms exceeding 10 mm was 10% at the 95% confidence level, due to the smaller number of gauges in the automated array and greater variability over shorter time periods. Spatial variation in throughfall was observed to increase steeply for small events (<10 mm), as was noted in other canopies (Kimmins, 1973), therefore results for In 2000, I net was 28.0, 69.4, and 18.0% of P G for the spring, summer, and autumn periods respectively; these are similar to values obtained in previous studies (McMinn, 1960;Rothacher, 1963). Table 3 shows that interception losses are highly temporally variable, and are correlated with event size, decreasing as event magnitude increases.…”
Section: Within-event Weather and Rainfall Variabilitysupporting
confidence: 89%
See 2 more Smart Citations
“…The confidence level for the mean of the total throughfall percentages for the storms exceeding 10 mm was 10% at the 95% confidence level, due to the smaller number of gauges in the automated array and greater variability over shorter time periods. Spatial variation in throughfall was observed to increase steeply for small events (<10 mm), as was noted in other canopies (Kimmins, 1973), therefore results for In 2000, I net was 28.0, 69.4, and 18.0% of P G for the spring, summer, and autumn periods respectively; these are similar to values obtained in previous studies (McMinn, 1960;Rothacher, 1963). Table 3 shows that interception losses are highly temporally variable, and are correlated with event size, decreasing as event magnitude increases.…”
Section: Within-event Weather and Rainfall Variabilitysupporting
confidence: 89%
“…Previous studies in old-growth Douglas-fir ecosystems in Oregon found I net to be 14% of gross precipitation for the months of October-April, and 24% of P G for the period from May to September (Rothacher, 1963). Studies of similar canopies on Vancouver Island, BC found annual I net to range from 20 to 40% of P G over a 5.5-year period (McMinn, 1960). I net from the same stands during the summer ranged from 30 to 57% of P G .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The Lysichitum community is present where soil is saturated by slowly moving ground water for much of the growing season. A si m i I a r ThujalL ysic hitum com m u n it y occurs in the coastal environment of Vancouver Island's Nanaimo River Valley (see McMinn 1960). Daubenmire and Daubenmire (1968) recognized three western redcedar communities in northern Idaho.…”
Section: Treesmentioning
confidence: 99%
“…Redcedar growth rates seem to be impaired by a droughty soil-moisture regime or highly leached soils on Vancouver Island, British Columbia (McMinn 1960). Redcedar seems to grow slower than western hemlock but faster than Pacific silver fir.on coastal Douglas-fir sites (see Walters and Haddock 1966).…”
mentioning
confidence: 99%